1989
DOI: 10.1128/aac.33.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol resistance in Pseudomonas cepacia because of decreased permeability

Abstract: The mechanism of chloramphenicol resistance was examined in a high-level-resistant isolate of Pseudomonas cepacia from a patient with cystic fibrosis. We investigated potential resistance mechanisms, including production of chloramphenicol acetyltransferase, ribosomal resistance, and decreased permeability. This strain (MIC, 200 ,ug/ml) had no detectable chloramphenicol acetyltransferase activity. In in vitro translation experiments in which we compared the resistant isolate with a susceptible strain of P. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Inducible -lactam activity is a general property of Pseudomonas cepacia (Prince et al, 1988). Resistance to chloramphenicol was similar to those of clinical strains in the study of Burns et al (1989).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Inducible -lactam activity is a general property of Pseudomonas cepacia (Prince et al, 1988). Resistance to chloramphenicol was similar to those of clinical strains in the study of Burns et al (1989).…”
Section: Discussionmentioning
confidence: 77%
“…The importance of surveying resistant environmental strains is that under favourable situations, they may transfer their resistance plasmids to pathogens. The problem is especially serious in hospitals where the environment can be a factor in the selection of multiresistant strains (O'Brien andAcar, 1987, Prince et al, 1988;Bryan, 1989;Burns et al, 1989). If such organisms are present in medicaments, they could behave as opportunist pathogens and initiate an infection, particularly in immuno-compromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upstream of the four structural genes and oriented in the opposite direction is a sequence encoding a putative LTTR (ceoR). Transfer of a cosmid clone containing all five components of the ceo gene cluster into an antibioticsusceptible B. multivorans laboratory strain also transferred resistance to chloramphenicol, trimethoprim, and ciprofloxacin, but not resistance to the aminoglycosides or β-lactam antibiotics (16).…”
Section: Discussionmentioning
confidence: 99%
“…The first of these investigated the regulation of ceoR. The putative ceoR promoter region was fused upstream of the promoterless lacZ in the broad host range vector pDN19lacΩ (16), and the construct was introduced into strain PC121. PC121 is a B. cenocepacia clinical isolate that demonstrates salicylate production and antibiotic resistance induced by low iron concentrations, rather than constitutively, as seen in the wild-type strain K61-3.…”
Section: Figurementioning
confidence: 99%
“…Another less prevalent mechanism of chloramphenicol resistance, which does not involve modification of the compound, but rather its entry into the bacterial cell, has been appropriately termed nonenzymatic and has been observed principally in gram-negative bacteria. The genetic determinants of this mechanism are usually plasmid encoded, such as in Pseudomonas aeruginosa and in members of the family Enterobacteriaceae (6, 10-12, 16,23,26,35,46); resistance determinants of chromosomal origin were also reported in Haemophilus influenzae (5), Pseudomonas cepacia (4), and Salmonella typhi (60). In most instances, it was demonstrated that nonenzymatic chloramphenicol resistance involves a membrane permeability barrier and that porins appear to be deficient in some of these strains.…”
mentioning
confidence: 99%